Campursari Karya Manthous: Kreativitas Industri Musik Jawa dalam Ruang Budaya Massa - -, Wadiyo; Haryono, Timbul; -, R.M. Soedarsono; Ganap, Victor (PANGGUNG, 2012)
ABSTRACTÃÂ ÃÂ ManthousÃ¢â¬â¢s Campursari is a blend of Javanese gamelan pentatonic music with popular music in Indonesia which is based on Western diatonic music. The tones of gamelan and ÃÂ the ÃÂ frequencies of ÃÂ the ÃÂ tune ÃÂ are ÃÂ all ÃÂ transformed into ÃÂ diatonicÃÂ  tone frequency. However, theÃÂ  harmonization which isÃÂ  used isÃÂ  pentatonic harmony of Javanese gamelan. ManthousÃ¢â¬â¢s Campursari has succesfully become one of the major music industries since it is supported by three components, namely the organizers of the music productions, the current distribution of music productions, and the needs of the community. The role of mass media is also very helpful toward the existence of this work. News about ManthousÃ¢â¬â¢s and his Campursari spread out widely to the public ÃÂ through ÃÂ the ÃÂ mass ÃÂ media. ÃÂ In ÃÂ a ÃÂ relativelyÃÂ  short ÃÂ time ÃÂ of ÃÂ its ÃÂ emergence, ManthousÃ¢â¬â¢s Campursari has become a mass cultural Javanese music.ÃÂ ÃÂ Keywords: Campursari, mass culture, music industryÃÂ ÃÂ ABSTRAKCampursari karya Manthous adalah sebuah campuran dari musik pentatonik gamelan ÃÂ Jawa ÃÂ dengan ÃÂ musik ÃÂ populer ÃÂ di ÃÂ Indonesia ÃÂ yang ÃÂ mengacu ÃÂ padaÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ musikÃÂ  ÃÂ diatonisÃÂ  ÃÂ Barat.ÃÂ  ÃÂ NadaÃÂ  ÃÂ gamelanÃÂ  ÃÂ danÃÂ  ÃÂ frekuensiÃÂ  ÃÂ laguÃÂ  ÃÂ semuanyaditransformasikan menjadi nada frekuensi diatonis. Namun, harmonisasi yang digunakan adalah harmoni pentatonis gamelan Jawa. Campursari karya Manthous telah ÃÂ berhasilÃÂ  menjadi salah ÃÂ satu ÃÂ industri ÃÂ musik ÃÂ besar ÃÂ karena didukung oleh tiga komponen, yaitu penyelenggara produksi musik, distribusi produksi musik, dan kebutuhan masyarakat. Peran media massa juga sangat membantu terhadap keberadaan karya ini. Berita tentang Manthous dan Campursarinya menyebar secara luas di masyarakat melalui media massa. Dalam waktu kemunculannya yang relatif singkat, Campursari karya Manthous telah menjadi musik Jawa dalam ruang budaya massa.ÃÂ ÃÂ Kata kunci: Campursari, budaya massa, industri musikÃÂ